Lines of Descent and Dissent: Genealogy, Narrative, and the Upaniṣads - Lindquist, Steven E. (Religions of South Asia, 2011)
This paper analyses the three genealogical lists found in the Bṛhadāraṇyaka Upaniṣad, not only as ascriptions of authority for the White Yajurvedic tradition, but as integral to the literary production of this text. I analyse the theme of ‘inheritance’ in Upaniṣadic narratives and in genealogical lists and show how a comparison of the two allows for a deeper understanding of the inclusion of genealogical lists in this text. In particular, I posit a new interpretation of the metronymic list found at the conclusion of Bṛhadāraṇyaka Upaniṣad 6, arguing that its ‘problematic’ form is not so problematic after all given its context.